Irish knit murder - Ehrhart, Peggy (Ehrhart, Peggy. Knit & Nibble mystery., 2023)
When seventy-something Isobel Lister, a harmless eccentric, is murdered after performing some beloved Irish songs at the senior center celebration, crafting magazine editor Pamela Paterson is on the case, and that means for the killer, the jig will soon be up.